Unraveled sleeve eaudiobook - Ferris, Monica (Needlecraft Mystery, 2011)
The art of needlecraft requires patience, discipline, and creativity. So too does the art of detection. Just ask Betsy Devonshire, who's learning that life in a small-town needlecraft shop can reveal an unexpected knack for knitting—and a hidden talent for unraveling crime. Betsy Devonshire has settled into her new home in Excelsior, Minnesota, as owner of the town's needlecraft shop. So why is she suffering from terrifying nightmares? She hasn't a clue but thinks it might help to get away for a while. With her friend Jill in tow, she heads north for a "stitch-in" at a remote, rustic lodge. But her nightmares only get worse—especially after she finds a dead woman no one else had seen. And when the body disappears, she knows she won't get any rest until she untangles the mysterious threads of the crime.